2006
DOI: 10.1002/mnfr.200500101
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of black tea theaflavin derivatives on 12‐O‐tetradecanoylphorbol‐13‐acetate‐induced inflammation and arachidonic acid metabolism in mouse ears

Abstract: Tea has been shown to possess several health beneficial properties primarily due to its polyphenolic content. The major polyphenolic compounds in black tea leaves are theaflavins (TFs) formed by oxidative coupling of catechins in tea leaves during its processing. In this paper, we report the characterization of 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced mouse ear inflammatory model and the inhibitory effects of major black tea TFs derivatives on this inflammation. In addition, the effect on inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 23 publications
4
47
0
1
Order By: Relevance
“…44 Theaflavin protected against inflammation in mice by inhibiting arachidonic acid metabolism via both 5-lipoxygenase and cyclooxygenase pathways. 45 Sesamin inhibited lipopolysaccharide-induced interleukin 6 production by suppression of the p38 mitogen-activated protein kinase signal pathway and nuclear factor-B activation. 46 Our results showed that quercetin and theaflavin significantly inhibited the ex vivo production of proinflammatory LTB 4 in the vasculature of the ApoE Ϫ/Ϫ mice and were better inhibitors of vascular LTB 4 production than (Ϫ)-epicatechin and sesamin ( Figure 4C).…”
Section: Apoementioning
confidence: 98%
“…44 Theaflavin protected against inflammation in mice by inhibiting arachidonic acid metabolism via both 5-lipoxygenase and cyclooxygenase pathways. 45 Sesamin inhibited lipopolysaccharide-induced interleukin 6 production by suppression of the p38 mitogen-activated protein kinase signal pathway and nuclear factor-B activation. 46 Our results showed that quercetin and theaflavin significantly inhibited the ex vivo production of proinflammatory LTB 4 in the vasculature of the ApoE Ϫ/Ϫ mice and were better inhibitors of vascular LTB 4 production than (Ϫ)-epicatechin and sesamin ( Figure 4C).…”
Section: Apoementioning
confidence: 98%
“…They cannot be isolated into pure compound under LH-20 chromatography. The composition ratio for TF2/TF29 was 3:1 after being quantified by the HPLC method [22].…”
Section: Preparation Of (-)-Epigallocatechin (Egc)mentioning
confidence: 99%
“…The theaflavins consist of theaflavin, theaflavin-3-gallate, theaflavin-3 0 -gallate and theaflavin-3,3 0 -gallate. Theaflavins have been suggested to reduce oxidative stress and inflammation in studies in vitro and in vivo [8][9][10][11][12][13][14]. However, although black tea is the most widely consumed beverage, the precise mechanisms by which black tea polyphenols exert these protective effects have not yet been as thoroughly elucidated as with green tea.…”
Section: Introductionmentioning
confidence: 99%